Pre‐Exposure of Human Adipose Mesenchymal Stem Cells to Soluble Factors Enhances Their Homing to Brain Cancer. (2nd February 2015) - Smith, Chris L.; Chaichana, Kaisorn L.; Lee, Young M.; Lin, Benjamin; Stanko, Kevin M.; O'Donnell, Thomas; Gupta, Saksham; Shah, Sagar R.; Wang, Joanne; Wijesekera, Olindi; Delannoy, Michael; Levchenko, Andre; et al.
Abstract : A reproducible, comprehensive, cell culture‐based approach to enhance human adipose mesenchymal stem cell (hAMSC) engraftment to brain tumors was developed. Pre‐exposing hAMSCs to glioma‐conditioned media and the extracellular matrix proteins fibronectin and laminin resulted in significant enhancements of the individual homing steps in vitro. This comprehensive, cell‐conditioning approach provides a novel method to enhance stem cell homing to gliomas and, potentially, other neurological disorders. Abstract : Recent research advances have established mesenchymal stem cells (MSCs) as a promising vehicle for therapeutic delivery. Their intrinsic tropism for brain injury and brain tumors, their lack of immunogenicity, and their ability to breach the blood‐brain barrier make these cells an attractive potential treatment of brain disorders, including brain cancer. Despite these advantages, the efficiency of MSC homing to the brain has been limited in commonly used protocols, hindering the feasibility of such therapies. In the present study, we report a reproducible, comprehensive, cell culture‐based approach to enhance human adipose‐derived MSC (hAMSC) engraftment to brain tumors. We used micro‐ and nanotechnological tools to systematically model several steps in the putative homing process. By pre‐exposing hAMSCs to glioma‐conditioned media and the extracellular matrix proteins fibronectin and laminin, we achieved significant enhancements of the individual homing steps in vitro. This homing was confirmed in an in vivo rodent model of brain cancer. This comprehensive, cell‐conditioning approach provides a novel method to enhance stem cell homing to gliomas and, potentially, other neurological disorders.